2006
DOI: 10.1007/s11373-005-9057-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitosin/CENP-F in mitosis, transcriptional control, and differentiation

Abstract: Mitosin/CENP-F is a large nuclear/kinetochore protein containing multiple leucine zipper motifs potentially for protein interactions. Its expression levels and subcellular localization patterns are regulated in a cell cycle-dependent manner. Recently, accumulating lines of evidence have suggested it a multifunctional protein involved in mitotic control, microtubule dynamics, transcriptional regulation, and muscle cell differentiation. Consistently, it is shown to interact directly with a variety of proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 84 publications
(153 reference statements)
0
54
0
Order By: Relevance
“…However, little is known about the relevance to rhabdomyosarcomagenesis of the candidate genes we identified located within these genomic regions. Among the genes found overexpressed, CENPF encodes a multifunctional protein which is involved in mitotic control and muscle cell differentiation (Ma et al, 2006). It has been found amplified and overexpressed in other tumor types (Pimkhaokham et al, 2000;van den Boom et al, 2003;Grutzmann et al, 2004) and is associated with Wilms tumor progression (Zirn et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the relevance to rhabdomyosarcomagenesis of the candidate genes we identified located within these genomic regions. Among the genes found overexpressed, CENPF encodes a multifunctional protein which is involved in mitotic control and muscle cell differentiation (Ma et al, 2006). It has been found amplified and overexpressed in other tumor types (Pimkhaokham et al, 2000;van den Boom et al, 2003;Grutzmann et al, 2004) and is associated with Wilms tumor progression (Zirn et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of different studies are not homogeneous as to the cell fate after CENPF silencing (Holt et al 2005, Laoukili et al 2005, Feng et al 2006. Ma et al (2006) suggest that this may be caused by different efficiencies of the mRNA silencing. We, however, agree with the hypothesis of Feng et al (2006), who assumed that the variation in results might be caused by the usage of different cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Although CENPF is initially known for its association with the centromere-kinetochore complex and chromosomal segregation, previous studies have demonstrated that CENPF may play a role in the regulation of the mitosis and proliferation of malignant cell growth, which are mediated by protein interactions (13,(29)(30)(31)(32). Thus, the actual functional role of CENPF is more elusive and complex.…”
Section: Irs Of Cenpf In Our Cohortmentioning
confidence: 99%